Pemecahan Masalah Geometri Berdasarkan Pendekatan Metakognitif Pada Aspek Perencanaan - Sastrowijoyo (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2021)
This study aims to determine students' ability in solving geometric problems through a metacognitive approach to the planning aspect. The approach used is qualitative descriptive type. The subjects of this study consisted of three grade VIII students of SMP Negeri 2 Benjeng Gresik who were included in the medium category. Data collection was carried out by means of instrument testing and interviews. The validity of the instrument in this study was the validity of the items and showed the respective values ​​of 0.74; 0.78; 0.76 which meant that the three items had fulfilled the validity. Whereas for the reliability test the results obtained were 0.76. The results showed that the planning aspects of the students were in the middle category of solving different geometric problems, this was influenced by the abilities of the students and the habitual factors in problem solving activities